2021
DOI: 10.3390/v13101997
|View full text |Cite
|
Sign up to set email alerts
|

Pericarditis after SARS-CoV-2 Infection: Another Pebble in the Mosaic of Long COVID?

Abstract: With the emerging success of the COVID-19 vaccination programs, the incidence of acute COVID-19 will decrease. However, given the high number of people who contracted SARS-CoV-2 infection and recovered, we will be faced with a significant number of patients with persistent symptoms even months after their COVID-19 infection. In this setting, long COVID and its cardiovascular manifestations, including pericarditis, need to become a top priority for healthcare systems as a new chronic disease process. Concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
0
25
1
1
Order By: Relevance
“…The main pathological features of COVID-19 mediated myocardial damage in convalescing patients often differ from classical viral-mediated myocarditis particularly in subjects with less severe disease ( 73 ) ( Figure 1 ). Characteristics of acute phase COVID-19 like pericarditis are infrequently observed ( 74 ). Thus, the adoption of the Lake Louise criteria applied extensively for myocarditis definition ( 38 , 39 ), may not always be suitable in the setting of convalescent COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological features of COVID-19 mediated myocardial damage in convalescing patients often differ from classical viral-mediated myocarditis particularly in subjects with less severe disease ( 73 ) ( Figure 1 ). Characteristics of acute phase COVID-19 like pericarditis are infrequently observed ( 74 ). Thus, the adoption of the Lake Louise criteria applied extensively for myocarditis definition ( 38 , 39 ), may not always be suitable in the setting of convalescent COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that although some authors have reported major cardiac abnormalities after recovery of COVID-19 infection, such as depressed LVEF [ 45 ], pericarditis, and pericardial effusion [ 46 , 47 ], these findings have not been detected in most majority of publications to date [ 5 , 36 42 ]. A possible explanation for these findings is that these are predominantly case reports or case series with small sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 13 PCS-related pericardial effusion alone was unlikely to explain her chest pain, dyspnea, and palpitations. 14 …”
Section: Discussionmentioning
confidence: 99%